(untitled) (Constructionism Conference Proceedings, 2025)
This workshop is based on theater improvisation according to G. Czerny (2017) and the methods of digital making (Ingold & Maurer, 2021). In this session, we will teach the connection between theater improvisation and physical computing created with the help of digitally controlled props. The concept of “Informatiktheater” is based on pre-programmed objects. The participants receive a digital prop, examine the interaction and behavior of the object and give it a theatrical meaning. From this, they create their own theater scene. Only then do they learn the basics of the Micro:bit. They assign the sensors and actuators used to the behavior of their prop and get to know the corresponding code. The physical experience of playing is directly assigned to the IT system. The participants now adapt the code of their prop to their scene. Theater and programming are developed iteratively until the scenes can be performed in front of an audience. By merging computer science and theater, this collaborative and creative coding process leads to the creation of a small-scale performance that showcases the potential of this combination. The concept of ‘Informatiktheater’ combines drama education with digital teaching methods, making programming more accessible and enjoyable, especially for children and young people who struggle with IT topics. This unique combination makes it possible to teach participants IT skills as well as social and performance skills in a creative environment. Programming should be perceived as a means of artistic expression. The plan is to further develop the concept so that the props can also be programmed with Python in order to appeal to older participants. The method and hardware will be described so that teachers can also carry out projects without specialising in computer science and drama. The workshop is suitable for teachers, education managers and those interested in developing new educational formats. Participants will not only enhance their programming skills, but also discover fresh opportunities for creative design and storytelling.